The role of Running-oriented Charity Fundraising and its Application for Světlo pro svět NPO - Knespl, Vojtěch (2016)
This master thesis analyses the role of running charity fundraising and its impact on non-profit organizations. It discovers the impact of various non-profit marketing and fundraising methods to address the donors, both current and prospective. First part of the thesis is focusing on explanation of key terms and concepts of non-profit organizations. It also describes what the position of marketing in the nonprofit sector is and how the fundraising is done. Author then identified the main fundraising methods in which non-profit organizations use running to make an impact. All identified types are supported by the real life examples. An intensive mapping of running oriented charity events in the Czech Republic and its deep analysis has helped author to identify what are the key success factors to be used when designing a new fundraising or marketing plan linked to running initiatives for Světlo pro svět NPO.